Welfare Restructuring in Russia since 2012: National Trends and Evidence from the Regions. Issue 1 (2nd January 2022) - Matveev, Ilya; Novkunskaya, Anastasia
Abstract: The purpose of this article is to place developments in welfare policy since 2012 in the context of the different models of welfare restructuring in Russia. We focus on President Vladimir Putin's Decree No. 597, which set out to raise the salaries of doctors, teachers and other categories of public employees. We find that neoliberalism is deeply embedded in policy practice. Furthermore, in order to examine the local effects of national trends in welfare restructuring since 2012, we present a case study of maternity care services in two Russian regions.